Wastewater, solid waste and environmental education: a discussion about the subject - Beltrame, Thiago Favarini; Beltrame, Alex Favarini; Lhamby, Andressa Rocha; Pires, Victor Paulo Kloeckner (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
In this paper is realized a literature study on environmental education to verify the contribution of the same for the theme of solid waste and wastewater. It focused on the bibliography of various authors so that they could carry out an interaction between environmental education and concepts that concern the treatment of wastewater and solid waste. At the end of the placements was possible to perceive that environmental education can be an ally of organizations and citizens regarding the preservation of the environment.